Estrutura e qualidade ambiental dos riachos costeiros na ictiofauna e suas redes tróficas de uma região neotropical - Santos, João Alberto Paschoa dos (2019)
To determine the composition, distribution and trophic relations between fish species in streams located in Bertioga-SP sandbank and to evaluate if the environmental characteristics influence this system are the main objectives of this thesis. Fish from 11 clearwater and darkwater streams were sampled using electric fishing over a year. The stomachs of the 11 most abundant species of the 26 species recorded throughout the study were analyzed. The unique species of clearwater streams were Acentronichthys leptos, Characidium japuhibense, Characidium lanei, Kronichthys cf. heylandi, Pseudotothyris obtusa, Rhamdioglanis frenatus, in addition to the marine / estuarine species Awaous tajasica, Centropomus parallelus and Dormitator maculatus, while only Hyphessobrycon bifasciatus was unique in blackwater environments. The trophic webs were similar in the streams comparing the dry and rainy periods. Allochthonous and autoctone organic material was similarly consumed among fish species, showing no preference for origin. The species with the highest number of relationships were Gymnotus pantherinus, Mimagoniates microlepis and Hollandichthys multifasciatus. Spintherobolus broccae is endangered. Thus, the preservation of the Conservation Units Serra do Mar State Park and Restinga de Bertioga State Park are important, as they are home to species that were important for the energy relations in the nutrient cycling of the system, besides being an important region with a wide diversity and thus providing relevant ecosystem services.